Turning a multimedia language lab into a powerful learner-centred tool - Gabarre, Cecile; Gabarre, Serge (2009)
In a learner-centred approach, lecturers constantly adapt their teaching methods to better suit their students‟ goals and needs. Ideally, the gathering of information relies on three channels: questionnaires and surveys, learners‟ log book and course evaluation. However, these methods can be time consuming or even impossible considering the nature and size of the class or even the constraints of limited contact hours.